Pengaruh Bimbingan Kelompok dengan Konseling Realitas terhadap Perilaku Asertif Peserta Didik - Bawamenewi, Sri Kasih Elviana; Lase, Famahato; Damanik, Hosianna Rodearni; Lase, Justin Foera-era (Lembaga Intelektual Muda (LIM) Maluku, 2026)
This study aims to examine the effect of group guidance integrated with reality counseling on the assertive behavior of students at SMP Negeri 4 Gunungsitoli Selatan. The research applies an associative quantitative approach using multiple linear regression analysis to test the proposed hypotheses. The population consists of 158 students enrolled at the school, while the sample was selected through purposive sampling, specifically Class VIII-A with a total of 28 students. Data were collected using a closed-ended questionnaire and analyzed through multiple linear regression to determine both simultaneous and partial effects of the independent variables on assertive behavior. The findings indicate that group guidance combined with reality counseling is highly effective in enhancing students’ assertive behavior. Prior to the implementation of the intervention, students’ assertive behavior was categorized as low. After receiving the group guidance service based on reality counseling principles, their assertive behavior significantly improved and reached a very good category. The analysis demonstrates a statistically significant influence, both jointly and partially, confirming that the intervention contributes meaningfully to the development of students’ assertiveness.